Development of entry-level competence tests : a strategy for evaluation of vocational education training systems - Schütte, Marc [Verfasser]; Spöttl, Georg [Verfasser] (My University, 2011)
"Developing countries such as Malaysia and Oman have recently established occupational standards based on core work processes (functional clusters of work objects, activities and performance requirements), to which competencies (performance determinants) can be linked. While the development of work-process-based occupational standards is supposed to have a positive effect on human resource development and economic prosperity, a continuing problem is associated with the evaluation of such standards. Evaluation of occupational standards has two angles of interest: (a) competence assessment (considering approval of workers); and (b) matching analysis (considering the difference between standard and work-process structures). The working hypothesis of this article is that occupational entry-level tests, an established means of competence assessment, can be utilised for matching analysis - that is, item development and field tests can provide qualitative and quantitative feedback about the relationship between standard structures and the requirements of current work-process structures. The article reflects experiences from the Sultanate of Oman. In particular, the text describes the strategy of (classical) test development and presents exemplary results. The final conclusion is that test development is a feedback mechanism and a decision-making resource linking prospective standards with the status quo in VET systems and related economic sectors." (Authors' abstract, BIBB-Doku)
Keywords: S System beruflicher Bildung; S 2.2.5 Standards in der beruflichen Bildung; L 1.1 Curriculumformen; L 8 Diagnostik / Eignung; L 6.2.3 Evaluation; I 1.1 Systemberatung; I 2.3.4 Asien; Berufsbildungssystem; Bildungsstandards; Arbeitsprozessorientierung; Kompetenzbewertung; Testverfahren; Evaluation; Systemberatung [Berufsbildung]; Entwicklungsländer; Oman